2019
DOI: 10.1177/2167479519893332
|View full text |Cite
|
Sign up to set email alerts
|

Self-Representations of Women’s Sport Fandom on Instagram at the 2015 FIFA Women’s World Cup

Abstract: The purpose of this study is to investigate how fans of women’s sport are using Instagram to self-represent their fandom. It uses the 2015 FIFA Women’s World Cup (WWC) as a case study to examine the ways in which fans at a women’s sport event express their fandom through images and to consider the social and political dimensions of using Instagram for promoting women’s sport. Instagram pictures containing the event-related hashtags #FIFAWWC, #LiveYourGoals, #SheBelieves, and #CanadaRed were collected over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Likewise, the number of likes given by both fans and athletes to the female Instagram sports content is quite high (Gönkek, 2019).This may be leading female athletes to gain likes by documenting their memories of their lives on the app. Analyzing fan images of women's football available on Instagram, Toffoletti et al (2021) suggested that the process of creating and sharing visual content with an intention to document fans' self-identity has become a routine fan activity during major sporting events. This may relate to the female respondents in this research who want to document, in a similarly way, their sports-related content, which involves a large part of their lives, via the content they produce for Instagram.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the number of likes given by both fans and athletes to the female Instagram sports content is quite high (Gönkek, 2019).This may be leading female athletes to gain likes by documenting their memories of their lives on the app. Analyzing fan images of women's football available on Instagram, Toffoletti et al (2021) suggested that the process of creating and sharing visual content with an intention to document fans' self-identity has become a routine fan activity during major sporting events. This may relate to the female respondents in this research who want to document, in a similarly way, their sports-related content, which involves a large part of their lives, via the content they produce for Instagram.…”
Section: Discussionmentioning
confidence: 99%
“…This study argues that the platform allows opportunity for wider variety of personalities and overlapping relationship between public and private as well as forging relationship [7]- [9]. The production of content and sharing visual content applied to niche interest in Instagram, suggesting that the world has greater recognition to the practice of Instagram users [10]. However, the utilization of Instagram by politicians proven to be more successful compared to the political institution as well as "communitainment" [11] [12].…”
Section: Introductionmentioning
confidence: 94%
“…In these posts, Danish Twitter users extend the party to the Twittersphere by joyfully presenting themselves as "being there" (Toffoletti et al, 2021) as part of the event. This illustrates how the travelling Tour invokes a spectacular space, a "yellow fever" transforming people and landscape.…”
Section: Participatory Tweetsmentioning
confidence: 99%